2018
DOI: 10.1080/19476337.2018.1513955
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and rheological properties of gum seed and pulp from Hymenaea courbaril L.

Abstract: The aim of this work was to isolate pulp (PH) and seed hydrocolloids (SH) of the fruit of Hymenaea corbaril L. and determinate chemical, functional and rheological properties, as a proposal of a new attractive product for functional applications in food systems. Both hydrocolloids have a high content of carbohydrates, minerals and fiber. The solubility of PH was higher 94.1%. The emulsifying capacity of SH, PH and GG increases with the hydrocolloid concentration. The emulsions showing a good stabilization stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(40 reference statements)
2
0
0
Order By: Relevance
“…G' and G" values of the samples at all concentrations increased with the increase of angular velocity. Similar behavior was reported for locust bean gum (Dakia et al, 2008) Hymenaea courbaril L. gum seed (Hernández-Morales et al, 2018). Figure 5 demonstrated that the RSG solutions at all concentrations G' were higher than Gʹʹ indicating that RSG showed solid viscoelastic character like gel behavior with all in frequency ranges.…”
Section: Dynamic Shear Propertiessupporting
confidence: 77%
“…G' and G" values of the samples at all concentrations increased with the increase of angular velocity. Similar behavior was reported for locust bean gum (Dakia et al, 2008) Hymenaea courbaril L. gum seed (Hernández-Morales et al, 2018). Figure 5 demonstrated that the RSG solutions at all concentrations G' were higher than Gʹʹ indicating that RSG showed solid viscoelastic character like gel behavior with all in frequency ranges.…”
Section: Dynamic Shear Propertiessupporting
confidence: 77%
“…In both mod behavior index values (n) exceed 1.0 (Table 3), which suggests that the solution beha as a dilatant fluid. This behavior aligns with shear thickening dispersions [23,51,52 characteristic observed when subject to a wide range of cutting rates [53][54][55]. Notably, behavior intensified with significantly increasing temperature (Figure 4a), likely tributed to the thickening capacity of the hydrogels and gums [53,56,57], although no nificant differences of n with SDH concentration and pH of the solution have been denced (p-value < 0.05).…”
Section: Rheological Analysissupporting
confidence: 79%